Profil Usaha Pengolahan Kopi Bali Tugu Sari Pajahan di Desa Pajahan, Kecamatan Pupuan, Kabupaten Tabanan - WULANDARI, SANG AYU DYAH ORCHID; WIDYANTARA, I WAYAN; AGUNG, I DEWA GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Business Profile of Bali Processing Coffee of Tugu Sari Pajahan in Pajahan Village, Pupuan Sub-District, Tabanan Regency. Tugu Sari Pajahan Bali Coffee Business is a coffee processing business that is accommodated by the Village Owned Enterprise. This study aims to determine the profile, income, and marketing of Tugu Sari Pajahan Bali Coffee business. This research was conducted at Tugu Sari Pajahan Bali Coffee Business. The time of this study was carried out for four weeks, namely in May to June 2018. The data used were qualitative and quantitative data with primary and secondary data sources and methods of data collection by interview, documentation, and library research.The profile in this study is a general description of Tugu Sari Coffee Business. The investment cost was Rp. 159,600,000.00, and the total cost used by Tugu Sari Coffee in 2017 was Rp. 133,883,500.00. Tugu Sari's Bali Coffee business production usually produces an average of 10 tons in one year. The large net income of Tugu Sari Pajahan Coffee business in 2017 was Rp. 45,225,950.00. Tugu Sari Pajahan Coffee Business in selling its products is by using re-sellers and directly selling to shops, stalls, and mini markets in the Tabanan, Denpasar, Badung and Buleleng areas.